PERANCANGAN SISTEM INVENTARIS BARANG BERBASIS WEB DENGAN FRAMEWORK LARAVEL PADA SMK NEGERI 7 KABUPATEN TANGERANG - Frely Cristiadzi Fawaz; Ilhan Fauzan; Sahidin (Journal of Research and Publication Innovation, 2023)
The Practical Work course is one of the mandatory courses for all students at the Faculty of Computer Science, Pamulang University. This practical work activity aims to get to know the scope of work in the field and provide practical work experience to students so that they can more easily adapt to the work environment when they graduate from college. This activity was carried out for 3 months at SMK Negeri 7 Tangerang Regency which is located at jln. Raya Legok Perum Dasana Indah, kec. Kelapa Dua Kab. Tangerang, Tangerang Regency. This report discusses the design and implementation of a web-based inventory system using the Laravel framework at SMK Negeri 7 Tangerang Regency, especially in the Teaching Factory of the Hospitality Department. The main goal of this system is to increase efficiency and accuracy in managing inventory data. This system is designed to provide convenience in recording, monitoring and reporting stock in real-time. The results of this research show that a web-based inventory system can improve the inventory management process at SMK Negeri 7 Tangerang Regency, especially in the Teaching Factory of the Hospitality Department, provide information on data collection of goods quickly and accurately and avoid wasted resources.